دراسة الأغشية الرقيقة لكبريتيد الرصاص المطعمة بالنحاس والمحضرة بطريقة الحمام الكيميائي - زلاسي, صفاء (universty of elouedجامعة الوادي, 2021)
تم تحضير الأغشية الرقيقة PbS باستخدام طريقة الترسيب بالحمام الكيميائي على ركائز زجاجية.حيث تم استعمال أسيتات الرصاص كمصدر لأيونات الرصاص (Pb+2) والثيوريا كمصدر لأيونات الكبريتيد (S-2) بتركيزات مولية ثابته في محلول الترسيب، وتم التغيير في نسبة التطعيم بالنحاس (0-2-4-6)% باستعمال أسيتات النحاس، تم إضافة ثلاثي الايتانول امين كمعقد. ساعة واحدة كان زمن الترسيب و 55°C كانت درجة الحرارة الترسيب. تمت دراسة الخصائص البنيوية للأغشية الرقيقة باستخدام حيود الأشعة السينية يمكن أن نلاحظ من نمط XRD أن تركيز النحاس المنخفض (2%) يحسن بشكل كبير من تبلور PbS. ومع ذلك، مع زيادة تركيز النحاس تنتج أغشية رقيقة بالمزيد من العيوب و الاجهادات، والتي لها تأثير سلبي على تبلور أغشية الـ PbS. وجد أن الحجم الحبيبي يزداد أولا ليصل قيمة عظمى عند نسبة تطعيم %2 ثم يتناقص مع زيادة تركيز النحاس. يعتقد أن إدخال النحاس بكمية معتبرة يقيد نمو البلورات. التطعيم بالنحاس أدى إلى تناقص في سمك الأغشية المحضرة. إن إدخال ايون النحاس يؤدي إلى توسيع فجوة النطاق، وكذلك إلى زيادة النفاذية ،حيث لاحظنا أن النفاذية تزداد بزيادة نسبة التطعيم. تقودنا النتائج التي توصلنا إليها إلى استنتاج أن كمية معتدلة من الشوائب النحاسية يمكن أن تسبب تحولات طفيفة في موضع أيونات الرصاص، وتزيل بعض الاضطرابات، وتعزز استقرار الشبكة.Nanocrystalline PbS thin films were prepared using chemical bath deposition method on glass substrates, together with lead acetate as a source of lead ions (Pb2+) and thiourea as a source of sulfide ions (S2-) with constant molar concentrations. Different concentrations of Cu-were used to dope the PbS films, copper acetate was used as a source of Cu, triethanolamine (TEA) was used as a complexing agent. One hour was the deposition time, and 55°C was the temperature of the bath. The structural properties of thin films were studied using X-ray diffraction. It can be seen from XRD pattern that the lower Cu concentration 2% greatly improves the crystallinity of PbS. However, as the Cu concentration increases, the nanofilm produce more defects and strains, which has an adverse effect on the crystallinity of the PbS nanofilms. The values of the crystallite size of the films increased to reach its maximum value at 2% then decreasedas the Cu concentration increases. It is believed that the introduction of copper in a considerable amount restricts the growth of crystals. The introduction of the copper ions leads to a decrease in the thickness of the prepared films and expansion of the band gap. Its well noticed that the transmittance of the films increases with the increase of the concentration of Cu. The obtained results lead us to conclude that a moderate amount of copper impurities can cause slight shifts in the position of the lead ions, remove some strains, and enhance the stability of the lattice.
مذكرة تخرج ماستر فيزياء
Keywords: الأغشية الرقيقة - لكبريتيد الرصاص (PbS); Thin films - lead sulfide (PbS)